EFFECT OF GUP ON THE RADIAL COMPONENT OF THE KINETIC ENERGY - Ahmadi, Fatemeh; Karimizadeh, Narges (MATTER: International Journal of Science and Technology, 2015)
Various theories of quantum gravity predict modifications of the Heisenberg uncertainty principle near the Planck scale, known as the generalized uncertainty principle (GUP). In this work, we study the effects of GUP on the equation of motion of a particle. Here, GUP preserves the rotational symmetry of the space-time. Then, considering the Kepler potential, we investigate the orbit motion of a particle and obtain the contribution of the radial component of the kinetic energy in this model.